Running on the edge: hematological responses to a non-stop ultramarathon with a focus on nitric oxide–mediated red blood cell deformability - Grau, Marijke; Bruns, Jonas; Stücher, Magnus; John, Lucas; Munk, Moritz; Siebers, Michael; Siebers, Christoph; Bloch, Wilhelm; Bizjak, Daniel A. (Frontiers in Physiology, 2025)
Background/ObjectiveUltramarathon competitions represent an extreme challenge for the human body, stressing physiological systems. However, little is known about their effects on the red blood cell (RBC) system, particularly on RBC deformability. Moreover, potential modulators of RBC deformability, such as oxidative stress and nitric oxide (NO) signaling, have not yet been systematically investigated in the context of ultramarathon running. The aim of the study was to assess alterations in these parameters following a 230 km non-stop ultramarathon, complemented by hematological parameters and markers of hematological stress to uncover mechanistic links.MethodsThe investigation was conducted during the 2024 TorTour de Ruhr®. Twelve runners completed the race (3f/9m; mean age: 48.1 ± 6.9 years; 177.6 ± 8.0 cm; 71.3 ± 13.7 kg). Anthropometric data and venous blood sampling were collected pre- and post-race and analyzed using paired statistics.ResultsBody weight as well as blood, plasma and RBC volumes remained unchanged. Post-race, mean corpuscular volume (MCV) and RBC distribution width (RDW) decreased, whereas mean corpuscular hemoglobin (MCH) and MCH concentration (MCHC) increased. These hematological shifts were associated with a leftward shift of the osmotic deformability curve, suggesting reduced RBC volume that could, over time, compromise cell integrity. Although acute hemolysis was not evident, significantly reduced haptoglobin levels indicate considerable cellular stress and raise the possibility of delayed hemolysis, warranting follow-up investigations. Importantly, RBC deformability improved post-race and was paralleled by elevated NO concentration, increased RBC-NO synthase activation, and enhanced S-nitrosylation of spectrins. These findings point toward activation of the RBC-NO pathway in response to mechanical stress, potentially supporting microcirculatory function. RBC free radicals decreased and total antioxidant capacity increased, suggesting a balanced redox response.ConclusionOverall, the ultramarathon induced complex but compensatory adaptations in the RBC system, where NO-mediated improvements in deformability may counteract stress-induced risks to cell integrity. Thus, despite no acute impairment of RBC function, adequate hydration, antioxidant-rich nutrition, and sufficient recovery may be emphasized to safeguard long-term RBC health in extreme endurance exercise.